Activity-based evaluation of ship pollutant emissions considering ship maneuver according to transportation plan - You, Youngjun; Lee, Joon Chae (International journal of naval architecture and ocean engineering, 2022)
Ships that use fossil fuels produce pollutant emissions that significantly affect air quality, global climate change, disruption of marine ecosystems, loss of coastline, and devastation of human health. Thus, it is important to manage maritime pollutant emissions. The first step to manage marine pollutant emissions is to precisely evaluate the emitted quantities. This paper presents the construction of a new approach to evaluate pollutant emissions of CO2, SOX, NOX, HC, CO, and PM using an activity-based approach by simulating an autopiloted ship for a transportation plan. The evaluated pollutant emissions were analyzed according to the fuel type, draft condition, and command speed. The evaluated emissions using the suggested approach were compared with those using a simplified approach, which shows the benefit of using LNGF for CO2, SOX, and CO in comparison to HFO. Potential drawbacks for NOX, HC, and PM emissions were also recognized for some conditions. •This paper has presented a new approach to evaluate pollutant emissions from the activity-based approach.•Feasibility of the activity-based approach was confirmed by comparing the values acquired from the suggested approach.•Beneficial reductions of CO2, SOX, and CO emissions when using LNGF were confirmed in comparison to those when using HFO, regardless of operation mode.•Drawbacks for NOX, HC, and PM emissions when using LNGF were recognized in comparison to those when using HFO.